Desempenho de híbridos simples e triplos de algodão herbáceo, Gossypium hirsutum L. r. latifolium Hutch, sintetizados a partir de um sistema restaurador de macho-esterilidade citoplasmática - Barboza, Giovanni Perazzo (1985)
A comparative study of the effect of the heterosis and combining ability on single and three-way crosses of the upland cotton, Gossypium hirsutum L., synthetized from a citoplasmic male-sterility restorer system, was conducted in 1982. The experiment was carried out at the Fazenda Experimental Vale do Curu, Pentecoste, Ceará, under irrigation, with randomized blocks as statistical design, comprising 55 treatments and 3 replications. [...]